2012
DOI: 10.1177/0194599812439664
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Skip Nodal Metastasis Is Rare in T1 and T2 Oral Tongue Squamous Cell Carcinoma

Abstract: Skip metastasis is rare in T1 and T2 oral tongue squamous cell carcinoma. Inclusion of level IV is not mandatory in selective neck dissection for clinically and radiologically negative neck disease in early tumors (T1 and T2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Currently, the management of level IV is not clear in clinically N0 oral cavity cancer, given the discrepancy between the frequently reported low incidence of metastases in level IV and the occurrence of neck recurrences because of skip metastases to this level. However, when other levels are not involved, routine inclusion of this level in selective neck dissection may not be justified owing to the low incidence of isolated nodal metastasis at level IV in these tumors . There is a general consensus that level V should not be included in the neck dissection in these patients because level V is rarely involved in oral cavity cancers …”
Section: Introductionmentioning
confidence: 99%
“…Currently, the management of level IV is not clear in clinically N0 oral cavity cancer, given the discrepancy between the frequently reported low incidence of metastases in level IV and the occurrence of neck recurrences because of skip metastases to this level. However, when other levels are not involved, routine inclusion of this level in selective neck dissection may not be justified owing to the low incidence of isolated nodal metastasis at level IV in these tumors . There is a general consensus that level V should not be included in the neck dissection in these patients because level V is rarely involved in oral cavity cancers …”
Section: Introductionmentioning
confidence: 99%
“…It is preferred for visualizing the parotid lesions on T1 weighed MRI because of hypertensive cause of the gland. MRI is chosen in case of meningeal symptoms as the leptomeninges are well explained with MRI than CT (Beltagi et al, 2019;Balasubramanian et al, 2012) Also it is shown as the consistent analyst about the malignancy or benignity of salivary gland.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Other studies have also shown a higher rate of spread to level IV in oral tongue cancer and have also advocated removal of this level [182,183]. Conversely, some investigators have found a much lower rate of spread to level IV, anywhere from 0% to 6.25% and recommend only level I to III dissection in cases of early oral tongue SCC [184][185][186][187][188][189][190]. The surgical anatomical distinction of level III versus level IV is the position of the omohyoid muscle.…”
Section: Surgical Therapymentioning
confidence: 99%